Data Adjustment for ARIMA Method to Investigate the Impact of Pandemic on Electricity Consumption Prediction in Indonesia - Wijaya, I Gede Putu Oka Indra; Kristi, Meilinda Santa; Maharani, Nabila Sri; Raharjo, Jangkung (Emitor: Jurnal Teknik Elektro, 2025)
Indonesia's rapid population growth and industrial expansion have significantly increased electricity consumption over the past decades. However, the COVID-19 pandemic has had a profound impact on the energy sector, causing a sharp decline in electricity demand. This disruption not only altered electricity consumption patterns but also forced a downward revision of the national electricity consumption target by approximately 10% compared to the government's initial projection. Understanding these shifts is crucial for ensuring sustainable energy planning and policy development. This study aims to analyze the impact of the pandemic on electricity consumption and forecast electricity demand in Indonesia from 2021 to 2045 using the Autoregressive Integrated Moving Average (ARIMA) method. Two forecasting scenarios are examined: one incorporating data from 2020 and another excluding it. The results indicate that excluding the 2020 data yields a more realistic projection, estimating electricity consumption to reach 610,807.8 GWh by 2045. The predictive performance of the ARIMA model is validated with statistical metrics, achieving an RMSE of 2,807.25, MAE of 1,481.25, and MAPE of 5.47%, with an overall accuracy of approximately 94.53%. These findings demonstrate that the ARIMA method is a robust and reliable tool for long-term electricity demand forecasting in Indonesia. The insights gained from this study provide valuable guidance for policymakers and energy planners in designing resilient and adaptive strategies to accommodate future electricity demand while considering the impacts of unprecedented disruptions such as pandemics.